1980
DOI: 10.1159/000260442
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Fluoride from Fluoride Dentifrices

Abstract: The bioavailability of fluoride (F) from NaF and Na2PO3F dentifrices was studied in detail in young volunteers. The method used was based on a comparison of plasma and urinary data obtained following intravenous administration of a single 3-mg dose F and ingestion of 6 g (6 mg F) of two different F dentifrices on three separate occasions. The plasma data indicated a higher degree of F bioavailability from the NaF dentifrice (111 ± 13%, SD, n = 4) as compared with theNa2P03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
1
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 9 publications
4
43
1
2
Order By: Relevance
“…Similarly, an increase of 50% would be expected for group B, while an increase of only 23% was seen. This apparent discrepancy may be explained by a combination of factors: differences in absorption of NaF compared to MFP [Forsman and Ericsson, 1973;Ekstrand and Ehrnebo, 1980;Drummond and Curzon, 1985;Trautner and Einwag, 1989;Drummond et al, 1990]; reduced bioavailability if F is swallowed soon after eating [Trautner and Siebert, 1986;Trautner and Einwag, 1989]; overestimation of brushing frequency by mothers; loss of dentifrice from the mouth. Taken together, these possibilities seem to indicate that there is an overestimation of fl uoride intake from the dentifrice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an increase of 50% would be expected for group B, while an increase of only 23% was seen. This apparent discrepancy may be explained by a combination of factors: differences in absorption of NaF compared to MFP [Forsman and Ericsson, 1973;Ekstrand and Ehrnebo, 1980;Drummond and Curzon, 1985;Trautner and Einwag, 1989;Drummond et al, 1990]; reduced bioavailability if F is swallowed soon after eating [Trautner and Siebert, 1986;Trautner and Einwag, 1989]; overestimation of brushing frequency by mothers; loss of dentifrice from the mouth. Taken together, these possibilities seem to indicate that there is an overestimation of fl uoride intake from the dentifrice.…”
Section: Discussionmentioning
confidence: 99%
“…l, [12][13][14][15] The increased availability of fluorides in food has also been suggested. '3"112' Singer and his co-workers have indicated that the average daily fluoride intake for infants, two-year-olds, and young male adults is within the accepted range of 0.05 to 0.07 milligram per kilogram body weight and has not significantly changed over the past 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…Concern with this increase has led to several studies on reasons to identify the risk factors for fluorosis [Mascarenhas, 2000]. There is no doubt that fluoridated dentifrices contribute to the daily intake of F. In addition, an increase in plasma and urine F levels after the use of fluoridated dentifrices has been shown [Ekstrand and Ehrnebo, 1980]. Fluoride dentifrices are thought to be the most widely used delivery method of F in the world [Rølla et al, 1991].…”
mentioning
confidence: 99%